Колабораціонізм в Україні в умовах російської агресії: проблема правового визначення (Серія: Історія. Політологія, 2021)
Стаття присвячена проблемі правового визначення колабораціонізму в Україні в умовах російської агресії. Автор розглянув основні концептуальні підходи до визначення поняття «колабораціонізм», акцентувавши на необхідності відділення свідомої корисливої співпраці з ворогом від вимушеної. Встановлено визначення колабораціонізму в українському законодавстві, зокрема його ототожнення з державною зрадою. Досліджено процес пошуку шляхів законодавчого оформлення та криміналізації колабораціонізму через аналіз основних положень законопроєктів, поданих на розгляд Верховної Ради України з 2017 року. The article focuses on the problem of the legal definition of collaborationism in Ukraine in the context of Russian aggression. The need to ban collaborationism at the legislative level has been on the agenda since the occupation of Crimea and the war in Donbass. However, the normative definition of defecting to the aggressor's side and knowingly collaborating with the occupying authorities is debatable. This is because in the face of Russian aggression, loss of life and the need to restore state sovereignty, the state should normatively define this phenomenon and establish fair punishment, but on the other hand, the threat of punishment for collaborating with the enemy in the temporarily occupied territories hinders the processes of de-occupation and reintegration.The author reviewed the main conceptual approaches to the definition of collaborationism. It has not been found to have a single established definition either in international law, political circles or academic research. Based on the interpretations considered, the broad approach, which understands collaborationism as assisting the enemy in any way, and the narrow approach, which explains it solely as conscious and voluntary cooperation with the occupier to the detriment of the state, are highlighted.The definition of collaborationism in Ukrainian law has been established, in particular its identification with high treason, while noting that collaborationism includes more forms of cooperation with the occupier than are specified in the Criminal Code of Ukraine, especially given the "hybrid nature" of Russian aggression.The process of finding ways to legislate and criminalise collaborationism is explored through an analysis of the main provisions of the draft laws submitted to the Verkhovna Rada of Ukraine since 2017. The first draft laws needed considerable refinement, detailing the definitions of the term "collaborationism" itself, which were not self-sufficient and did not emphasise the voluntariness or consciousness of such activity. The draft laws of 2021, currently before the Verkhovna Rada, largely addresses these shortcomings by defining in detail all the forms of activity that should qualify as collaborationism, giving them a better chance of coming into force.Emphasis has been placed on the need for a balanced, cautious and clear interpretation of this concept in Ukrainian legislation that will ensure that appropriate and fair legal liability for this criminal offence is established, while not impeding the process of de-occupation and reintegration.